Urgensi Pengembangan Buku Dongeng Movable Berbasis Etnosains Sebagai Bahan Ajar Penunjang Pembelajaran Ipa Siswa Kelas - Izzah Muyassaroh; Titin Sunaryati (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Transforming textbooks into something interesting and fun for students is now increasingly interesting to study in line with the increasing number of challenges creating children's interest for reading. In order to have an attractive value for children, textbooks need to be specially prepared with a child's point of view which is of course adjusted to the character and level of children's development, learning needs, and the socio-cultural environment. This research is a descriptive qualitative study that aims to identify the urgency of developing ethnoscience based movable fairytale book to support science learning in grade IV Elementary students. This research is a descriptive qualitative study using observation, interview, and questionnaire techniques in data collection. The data analyzed using descriptive analysis techniques according to Miles & Huberman. The results of the study showed that textbooks that support learning are still limited, reading activities are the most preferred activity during learning but not in leisure, and ethnoscience-based movable fairytale book very hoped to be developed.